Impacts and Future Perspectives of Fertilizer Policy in Indonesia - Rachman, Benny; Sudaryanto, Tahlim (Analisis Kebijakan Pertanian, 2010)
The implementation of fertilizer subsidy policies have been applied comprehensively starting from the planning stage to fertilizer distribution system, including setting the highest retail price and the amount of subsidy. However, the policy has not been able to ensure adequate availability of fertilizers at the farm level. Planning on the amount of fertilizer demand is not fully accurate and supervision has not optimally implemented causing the distribution of subsidized fertilizer below the target. It is reported that farmers who manage less than 0.5 hectares of land received only 40 percent of the total subsidy and most farmers (90%) purchase subsidized fertilizer at prices higher than the highest retail prices. To overcome this problem, the government plan to change the distribution mechanism of subsidy from indirect subsidy to direct subsidy to farmers/ farmer groups. The expected impacts of that policy are: (1) farmers obtain direct benefits from fertilizer subsidies, (2) avoid disparity between the prices of subsidizedÂ  and non-subsidized fertilizers at the market, (3) reduce the possibility of scarcity of subsidized fertilizer supply, (4) improve cultural practices, especially in crops fertilizing, (5) increase the efficiency of using government subsidies, and (6) increase farmers income and welfare.